2019
DOI: 10.1039/c9dt02438g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structures and cytotoxic effects in vitro of cis- and trans-[PtIVCl4(NHC)2] complexes and their PtII precursors

Abstract: PhICl2 oxidises cis-/trans-[PtIICl2(NHC)2] complexes to stable, cancer-selective, cytotoxic cis-/trans-[PtIVCl4(NHC)2] complexes while H2O2 or NaOCl give [PtIVCl4−n(OH)n(NHC)2] complexes that decompose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…Second, the inhibitory effects of different platinum complexes did not correlate with their DNA-binding capability, or cancer cell toxicity. For example, the platinum(IV) complex TR425, which is distinctly less toxic to cancer cells than cisplatin, and binds only weakly to linear DNA (Rehm et al, 2019), had a similar inhibitory potency as cisplatin in our translocation assay. Third, complexes that are considered non-functional in terms of DNA-binding and anticancer activity, such as transplatin, still showed type IV secretion inhibition to a higher extent than cisplatin dissolved in DMF.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Second, the inhibitory effects of different platinum complexes did not correlate with their DNA-binding capability, or cancer cell toxicity. For example, the platinum(IV) complex TR425, which is distinctly less toxic to cancer cells than cisplatin, and binds only weakly to linear DNA (Rehm et al, 2019), had a similar inhibitory potency as cisplatin in our translocation assay. Third, complexes that are considered non-functional in terms of DNA-binding and anticancer activity, such as transplatin, still showed type IV secretion inhibition to a higher extent than cisplatin dissolved in DMF.…”
Section: Discussionmentioning
confidence: 77%
“…However, when we tested complexes in which the DMSO ligand was replaced by a second NHC ligand in cis configuration (Rehm et al, 2016), we found some with clear antibacterial effects toward H. pylori (data not shown), but also others which had similar properties as cisplatin or the DMSOcontaining complexes ( Figure 4C). Finally, we analyzed the effect of an analogous platinum(IV) complex with two NHC ligands, which exhibits reduced DNA-binding properties and only moderate cytotoxicity (Rehm et al, 2019). Here, we also observed a substantial inhibitory potential with respect to CagA type IV secretion for compound TR425, while H. pylori growth was not strongly affected ( Figure 4D).…”
Section: Effects Of Other Platinum Complexes On Type IV Secretion Inhmentioning
confidence: 77%
“…Similar results have been previously observed for the reactions of K 2 [PtCl 4 ] with other silver carbenes. 53 57 …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, two elementary reactions, oxidative addition and reductive elimination, are very important because of their major role in many catalytic processes. These reactions have been the subject of many studies, and organoplatinum­(II) and -(IV) complexes have been used to investigate their chemistry in detail. Most organoplatinum complexes used in this regard include N-donor (such as 2,2′-bipyridine) or cyclometalated (such as 2-phenylpyridinate) chelate ligands. These organoplatinum­(II) complexes having N^N or C^N ligands are highly reactive toward oxidative addition reactions, which typically proceed by an S N 2 mechanism, as has been confirmed experimentally and computationally. In contrast to many reports on the oxidative addition and reductive elimination of organoplatinum complexes bearing N^N or C^N chelate ligands, few studies have been reported on the reactivity of bis-NHC platinum complexes. , Bis-NHC chelate complexes of dimethylplatinum are rare. Jamali and co-workers prepared the complex [PtMe 2 (bis-NHC)] by the reaction of [PtMe 2 (μ-SMe 2 )] 2 with 1,1′-methylene-3,3′-bis­[( N -( tert -butyl)­imidazol-2-diylidene] in the presence of Ag 2 O .…”
Section: Introductionmentioning
confidence: 99%